Reversible Deposition and Dissolution of Magnesium from Imidazolium-Based Ionic Liquids - QingSong Zhao; Yanna NuLi; Tuerxun Nasiman; Jun Yang; JiuLin Wang (International Journal of Electrochemistry)
The electrochemical performance of six imidazolium cation-based ionic liquids (ILs) containing 0.3 mol L-1 Mg(CF3SO3)2 as the electrolytes for magnesium deposition-dissolution was examined by cyclic voltammogramms and constant current discharge-charge techniques. Scanning electron microscopy and energy dispersive X-ray spectroscopy measurements were conducted to characterize the morphologies and components of the deposits. The cathodic satiability of imidazolium cations can be improved by increasing the length of alkyls at the 1-position and introducing methyl group at the 2-position of the imidazolium cations. A reversible magnesium deposition-dissolution can be achieved at room temperature. After adding appreciate amount of tetrahydrofuran (THF) organic solvent, the conductivity and the peak currents for Mg deposition and dissolution can be significantly improved. The potential polarization of deposition-dissolution process is decreased using Mg powder electrode.